The burden of the past problems of historical perception in Japan-Korea relations - Kimura, Kan 1966- (Ann Arbor, MI University of Michigan Press, 2019)
"The Burden of the Past reexamines the dispute over historical perception between Japan and South Korea, going beyond the descriptive emphasis of previous studies to clearly identify the many independent variables that have affected the situation. From the history textbook debates, to the Occupation-period exploitation of "comfort women," to the Dokdo/Takeshima territory dispute and Yasukuni Shrine visits, Professor Kimura traces the rise and fall of popular, political, and international concerns underlying these complex and highly fraught issues. Utilizing Japanese and South Korean newspaper databases to review discussion of the two countries' disputed historical perceptions from the end of World War II to the present, The Burden of the Past provides readers with historical framework and the major players involved, offering much-needed clarity on such polarizing issues. By seeing behind the public discourse and political rhetoric, this book offers a firmer footing for a discussion and the steps toward resolution." -- Provided by publisher.
A theoretical framework for examining the historical perception dispute -- Three factors in the dispute over historical perceptions -- The history textbook issue -- The turning point of the 1980s -- Japan-South Korea relations at the end of the Cold War -- Issues of historical perception during Japan's "lost" twenty years --Revisiting the Japan-South Korea historical perception dispute.
"Originally published in Japan by Minerva Shobo, in 2014" --Title verso.
Includes bibliographical references and index.
Keywords: Japan -- Roreign relations -- Korea (South).; Korea (South) -- Foreign relations -- Japan; Japan -- Foreign relations -- 1945-.